Landslide risk analysis in the area North of Lisbon (Portugal): evaluation of direct and indirect costs resulting from a motorway disruption by slope movements - Zêzere, José (2019)
A risk analysis is developed for a test site located in the area north of Lisbon using a scenario of a temporary interruption of the motorway A9 due to a landslide of rotational or translational type. Landslide susceptibility is assessed at the regional scale independently for rotational and translational slides, comparing the landslide distribution with a set of assumed independent landslide predisposing factors. Susceptibility models are validated and classified through the computation of prediction rate curves based on the temporal partition of the landslide data sets. Landslide hazard maps are based on a scenario of future landslide occurrence for the next 27 years. These maps allow the definition of two critical areas on the motorway A9 with regards to landslide susceptibility. Direct costs associated with both critical spots are assessed taking into account the probable affected area of the motorway, and the reconstruction costs. Indirect costs derived from the traffic interruption are evaluated considering the alternatives paths to the motorway, and include costs resulting from: (1) additional fuel consumption; (2) decrease in tollgate income; and (3) loss of productive time. Results show that indirect costs may be 24 to 43 times higher than direct costs, assuming a temporary interruption of the motorway for 6 months.